A network meta-analysis evaluating valgization high tibial osteotomy cutting guides: improving surgical precision through navigation and PSI - Fanny Delaigue; Hassan Wardani; Jules Descamps; Matthieu Ollivier; Rémy Nizard; Pierre-Alban Bouché (Knee Surgery & Related Research)
Abstract Background A total of three techniques are used to guide tibial cuts in high tibial osteotomy (HTO): the conventional method, navigation systems, and patient-specific instrumentation (PSI). This network meta-analysis sought to assess whether any of these methods achieve better radiological outcomes, greater functional gains, or a reduced rate of complications. Design We included all controlled and noncontrolled trials comparing at least two of the surgical techniques. Primary outcomes were rates of medial proximal tibial angle (MPTA) and posterior tibial slope (PTS) outliers. Secondary outcomes included the rate of hip-knee-ankle (HKA) angle outliers, joint range of motion, postoperative clinical scores, and complication rates. Results The analysis included 24 studies with 1817 patients and 1951 operated knees. PSI did not reduce the rate of MPTA outliers compared with conventional techniques (95% credible intervals, CI [0.09–56.84]) or navigation (95% CI [0.03–25.62]), and navigation did not reduce the rate compared with conventional methods (95% CI [0.84–9.17]). Navigation reduced the rate of PTS outliers compared with conventional techniques (95% CI [1.93–1.56.104]). No study investigating PTS outliers with PSI was identified or included. Both navigation and PSI reduced the rate of HKA angle outliers (95% CI [1.33–3.16] and [1.15–42.61], respectively). Aside from the rate of HKA angle outliers and the Lysholm score between 1 and 2 years postoperatively, no differences were observed for other outcomes. Conclusions Navigation and PSI allow for more precise achievement of the PTS and HKA angle values set by the surgeons but do not affect long-term knee function or complication rates. However, the cost and limited availability of these techniques should be considered, especially in the absence of additional functional benefits.